Why Hazing?: Measuring the Motivational Mechanisms of Newcomer Induction in College Fraternities - McCreary, Gentry R. (Journal of cognition and culture, 2019)
Hazing behaviors as a part of group initiations have been theorized to contribute to a sense of group solidarity, to ensure loyalty and commitment of group members, to teach group-relevant skills and attitudes to group members, and to reinforce the social hierarchy within groups. In a survey of members of an international college fraternity (n=2833), researchers propose and test a four-dimensional model of hazing motivation. Using exploratory factor analysis, the proposed four-factor model explains 74 percent of the overall variance and confirmatory factor analysis demonstrated acceptable model fit. Correlation and regression analysis suggested that social dominance- motivated hazing is strongly associated with hazing tolerance, moral disengagement, and a variety of measures related to organizational commitment and attachment.